Re-ordering chaotic carbon : origins and application of textured carbon - Loh, G. C. (2013)
Formation of nanocrystals with preferred orientation within the amorphous carbon matrix has attracted lots of theoretical and experimental attentions recently. Interesting properties of this films, easy fabrication methods and practical problems associated with the growth of other carbon nanomaterials such as carbon nanotubes (CNTs) and graphene gives this new class of carbon nanostructure a potential to be considered as a replacement for some applications such as thermal management at nanoscale and interconnects. In this short review paper, the fabrication techniques and associated formation mechanisms of these nanostructured films have been discussed. Besides, electrical and thermal properties of these nanostructured films have been compared with CNTs and graphene.